Perspective: Acknowledging complexity to advance the understanding of developmental coordination disorder - Meachon, Emily J. (Frontiers in Human Neuroscience, 2023)
Developmental Coordination Disorder (DCD) is a heterogeneous neurodevelopmental disorder known for primary symptoms of motor learning and execution difficulties. Recent research has consistently suggested DCD symptoms span broadly beyond motor difficulties, yet a majority of research and practice approaches the investigation, diagnosis, and treatment of DCD with a reductionist framework. Therefore, this paper suggests the paradigm of complexity theory as a means for better conceptualization, assessment, and treatment of DCD. First, the perspective of complexity theory and its relevance to DCD is described. Then, examples from recent research which attempt to acknowledge and capture the complex nature of DCD are highlighted. Finally, suggestions for considering and measuring complexity of DCD in future research and practice are provided. Overall, the perspective of complexity can propel the research forward and improve the understanding of DCD relevant to assessment and treatment. The complexity paradigm is highly relevant to describing the evolving and multidimensional picture of DCD, understanding heterogeneous symptom profiles, making connections to interconnected secondary symptoms, and beyond.